Fatty Acid Compositions of Some Popular Grape Seeds Grown in Turkey - Akin, Aydin (Asian Journal of Chemistry, 2012)
The present study describes the determination and comparison of fatty acid profile in seeds of four popular wine grape cultivars (Narince, Kalecik Karasi, Öküzgözü and Bogazkere) grown in Turkey. The fatty acid profile was determined using GC. 13 Fatty acids were detected in grape seed oils. The results showed that w-6 fatty acid level of grape seed from Kalecik Karasi were higher than that of other grape cultivars.